A MATEMÁTICA NA MICROSCOPIA: UM RELATO DE EXPERIÊNCIA EXTENSIONISTA (REMUNOM, 2024)
This work describes the experience of a workshop given during National Science and Technology Week, 2017, with the theme: Mathematics is in everything! The proposed workshop was entitled "mathematics in microscopy" and was offered to Science and Biology teachers from public and private schools in the municipality of Teófilo Otoni, Minas Gerais. The experience within the workshop contributed to the improvement of primary school teachers in terms of using the microscope in practical classes, as well as highlighting the transversality of mathematics in this context. The activity provided reflection, sharing of experiences and exchange of knowledge in the face of a timeless difficulty in basic education: understanding the microscopic structure of the human body and the existence of a reality that is not captured by the resolving power of the human eye.